Confronting the low-scale seesaw and leptogenesis with neutrinoless double beta decay - J. de Vries; M. Drewes; Y. Georis; J. Klarić; V. Plakkot (Journal of High Energy Physics)
Abstract We revisit the impact of heavy neutrinos with masses in the MeV-GeV range on neutrinoless double beta decay (0νββ) in view of updated results for the lifetime of this process. Working in a minimal realistic extension of the Standard Model by two right-handed neutrino flavours, we show that the non-observation of 0νββ will impose strong bounds on the heavy neutrino properties that are complementary to the limits obtained from Big Bang Nucleosynthesis and collider searches. For an inverted mass hierarchy of the light neutrinos we find that improved limits on 0νββ from next-generation experiments, assuming an improvement of two orders of magnitude on the current 0νββ limits will restrict the allowed parameter space for fixed mass splitting to narrow bands in the mass-mixing plane. Further combining this with the requirement to explain the baryon asymmetry of the universe via leptogenesis reduces these bands to windows in parameter space that are constrained in all directions and can be targeted by direct searches at accelerators, and restricts the mass splitting to values that can be resolved at experiments. For a normal mass hierarchy, restricting the allowed parameter will require even stronger 0νββ limits, and only parts of the parameter space can then be probed.